Hidden nature - Roberts, Nora (New York : St. Martin's Press, 2025)
After surviving a near-fatal shooting, Natural Resources officer Sloan Cooper returns home to Heron$1 (Bs Rest to recover. Dumped by her boyfriend and determined to rebuild, she dives into a local missing persons case. Her investigation uncovers disturbing patterns$1 (Band proves she$1 (Bs far from finished as a protector and detective.s
Keywords: Kidnapping victims -- Fiction; Missing persons -- Fiction; Homecoming -- Fiction; Policewomen -- Fiction; Women detectives -- Fiction; Detectives -- Fiction; Man-woman relationships -- Fiction; Maryland -- Fiction; Detective and mystery fiction; Thrillers (Fiction)